The business climate in Uganda implications for job creation - Mawejje, Joseph (Economic Policy Research Centre (EPRC), 2013)
This brief is a summary of the findings of four business climate surveys conducted in the four quarters between April 2012 and March 2013. The purpose is to highlight the evolution of Uganda’s business climate and its implications for business expansion and employment creation. For each of the surveys we followed up and interviewed the same business establishments. Our results show that the business climate has been weak and declining in the last four quarters. In addition results show that businesses are operating below capacity and that under the current business conditions they are not likely to create new employment opportunities. Moreover, businesses have expressed dissatisfaction with the available labour force describing it as unproductive due to its perceived inadequate education, poor work ethic and insufficient capacity to innovate. We therefore make the recommendation that any measures geared towards creating employment opportunities should also consider ameliorating the business environment and equipping the labour force with the necessary skills to improve productivity.